2018
DOI: 10.1371/journal.pone.0207056
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble cranberry extract inhibits Vibrio cholerae biofilm formation possibly through modulating the second messenger 3’, 5’ - Cyclic diguanylate level

Abstract: Quorum sensing (QS) and nucleotide-based second messengers are vital signaling systems that regulate bacterial physiology in response to changing environments. Disrupting bacterial signal transduction is a promising direction to combat infectious diseases, and QS and the second messengers are undoubtedly potential targets. In Vibrio cholerae, both QS and the second messenger 3’, 5’—cyclic diguanylate (c-di-GMP) play a central role in controlling motility, motile-to-sessile life transition, and virulence. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Previous studies have confirmed that phenolic compounds from plants, such as eugenol, tea polyphenols, and thymol, can inhibit the production of virulence-associated factors and biofilm formation in P. aeruginosa ( Yin et al, 2015 ; Walsh et al, 2019 ; Antunes et al, 2021 ). Scanning electron microscopy results further demonstrated that paeonol decreased biofilm formation against P. aeruginosa , possibly interfered with the subsequent steps of surface adhesion or biofilm formation ( Pederson et al, 2018 ; Liu et al, 2019 ). Additionally, the motility of P. aeruginosa is a complex process that is co-regulated by the las and rhl systems to promote the formation and spread of biofilms ( Glessner et al, 1999 ).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have confirmed that phenolic compounds from plants, such as eugenol, tea polyphenols, and thymol, can inhibit the production of virulence-associated factors and biofilm formation in P. aeruginosa ( Yin et al, 2015 ; Walsh et al, 2019 ; Antunes et al, 2021 ). Scanning electron microscopy results further demonstrated that paeonol decreased biofilm formation against P. aeruginosa , possibly interfered with the subsequent steps of surface adhesion or biofilm formation ( Pederson et al, 2018 ; Liu et al, 2019 ). Additionally, the motility of P. aeruginosa is a complex process that is co-regulated by the las and rhl systems to promote the formation and spread of biofilms ( Glessner et al, 1999 ).…”
Section: Discussionmentioning
confidence: 86%
“…Eradication of biofilms is a serious global health concern in controlling bacterial infections because they cause microbial resistance to many antibiotics. 27 Although non-antibiotic therapeutic strategies do not develop antimicrobial resistance, to be effective, they should be able to penetrate the biofilm structure or inhibit biofilm formation by bacterial population. For the first time in this study, the antibiofilm activity of MSCs CM and MSCs CM-CS NPs against MDR V. cholerae strains was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of biofilm formation is preferred as a treatment option because extracellular polysaccharides make biofilms difficult to chemically remove from surfaces and can protect bacteria from antibiotics and other harmful environmental conditions [216][217][218]228]. In this regard, cranberry materials have been investigated for their ability to affect biofilm formation by a number of potential pathogens, and a range of effects and activities have been observed for different organisms and test environments (e.g., urine vs. saliva vs. juice) [63,[229][230][231][232][233][234]. This range of responses by different organisms may lead to either beneficial or harmful effects on overall human health, depending on both the bacteria present and the host environmental variables involved.…”
Section: Effects On Biofilm Formation and Bacterial Aggregationmentioning
confidence: 99%